2017
DOI: 10.1007/s00261-017-1444-5
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and magnetic resonance imaging of peripelvic and periureteric pathologies

Abstract: Peripelvic and periureteric areas are frequently overlooked in the imaging evaluations of the urinary system on computed tomography and magnetic resonance imaging. Several neoplastic and non-neoplastic disorders and diseases including lipomatosis, angiomyolipoma and angiolipomatous proliferation, vascular lesions, lymphangiomatosis, Rosai-Dorfman disease, Erdheim-Chester disease, extramedullary hematopoiesis, IgG4-related disease, lymphoma, mesenchymal tumors, trauma, and Antopol-Goldman lesion may involve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Gumeler and colleagues reported infiltrative renal hilar mass with ill-defined borders as a characteristic feature of renal RDD and suggested hypo-attenuated renal cortical nodules and subcapsular infiltration as other important imaging findings on CT. In the case described in their study, T1W and T2W imaging showed low signal intensity with mild enhancement on post-contrast images 14 . In 2019, Kmetz et al reported the most recent case of bilateral renal RDD in a 60-year-old Caucasian man with a history of anemia and thrombocytopenia of unknown etiology.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Gumeler and colleagues reported infiltrative renal hilar mass with ill-defined borders as a characteristic feature of renal RDD and suggested hypo-attenuated renal cortical nodules and subcapsular infiltration as other important imaging findings on CT. In the case described in their study, T1W and T2W imaging showed low signal intensity with mild enhancement on post-contrast images 14 . In 2019, Kmetz et al reported the most recent case of bilateral renal RDD in a 60-year-old Caucasian man with a history of anemia and thrombocytopenia of unknown etiology.…”
Section: Discussionmentioning
confidence: 74%
“…Although imaging studies are also not highly discriminative, they will help narrow the diagnosis. Modalities such as renal ultrasound, abdominopelvic CT, and MRI, along with FDG PET/CT scan could be considered as beneficial tools for identification of the lesion, evaluation of the extent of disease, image-guided biopsy, and even monitoring disease activity and response to therapy 14,15 . Due to the rarity of RDD, it is less likely for the urologist or radiologist to consider this diagnosis when observing an abnormal renal lesion on imaging; however, having a suspicion in mind might favorably change patient management and help prevent unnecessary nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Parapelvic areas and the renal sinus are the commonly affected anatomical areas. [ 5 ] In cases when they are located within the renal parenchyma, they can mimic multilocular cystic disease of the kidney. [ 5 ] Lymphangiomatosis may sometimes extend from the peripelvic area into the periureteric area.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] In cases when they are located within the renal parenchyma, they can mimic multilocular cystic disease of the kidney. [ 5 ] Lymphangiomatosis may sometimes extend from the peripelvic area into the periureteric area. Renal lymphangiomatosis is usually bilateral with only few reported cases being unilateral.…”
Section: Discussionmentioning
confidence: 99%
“…In the case described in their study, T1W and T2W imaging showed low signal intensity with mild enhancement on postcontrast images. 14 In 2019, Kmetz et al reported the most recent case of bilateral renal RDD in a 60‐year‐old Caucasian man with a history of anemia and thrombocytopenia of unknown etiology. Subsequent to identifying a left upper quadrant mass on palpation, CT scan was performed for the patient, revealing bilateral soft tissue masses in the perinephric space, measuring up to 22 cm on the left side.…”
Section: Discussionmentioning
confidence: 99%